In-flight allergic emergencies - Mario Sánchez-Borges; Victoria Cardona; Margitta Worm; Richard F. Lockey; Aziz Sheikh; Paul A. Greenberger; Ignacio J. Ansotegui; Motohiro Ebisawa; Yehia El-Gamal; Stanley Fineman; Mario Geller; Alexei Gonzalez-Estrada; et al. (World Allergy Organization Journal, 2017)
Abstract Allergic and hypersensitivity reactions such as anaphylaxis and asthma exacerbations may occur during air travel. Although the exact incidence of in-flight asthma and allergic emergencies is not known, we have concerns that this subject has not received the attention it warrants. There is a need to provide passengers at risk and airlines with the necessary measures to prevent and manage these emergencies. A review of the epidemiology, management and approaches to prevention of allergic and asthma emergencies during air travel is presented with the goal of increasing awareness about these important, potentially preventable medical events.